RELEVANSI KEUTAMAAN SPRITUALITAS MATIRAGA VINSENSIAN TERHADAP PELAYANAN KATEKIS - Mira, Chicentus Sixtusia; Dewantara, Agustinus Wisnu (Bahasa Indonesia, 2025)
This research aims to find out the relevance of the virtue of Vincentian asceticism to the catechist. Catechist is a group of lay in the Catholic Church who involves themselves in all aspects of the church, example: take charge of teaching, accompaniment, and services to all the categorical groups, and liturgical. This research applies qualitative methods, the methodology based on the literature review that analyses data from books, Articles, from The Holy Bible, and documents (library Research). This method aims to find the relevant virtue of asceticism in the services of them in the Catholic Church, teaches, guides, and serves the faithful. As a catechist, there is a need for self-denial and commitment. The result shown that the virtue of Vincentian Asceticism could help Catechists overcome the challenges in services. Additionally, it is also to deepen the spirituality of the catechist through preaching, living in the sacrament of the Eucharist, active in the church, faithfulness in the teaching.